2000
DOI: 10.2135/cropsci2000.402488x
|View full text |Cite
|
Sign up to set email alerts
|

Salinity Effects on Zoysiagrass Cultivars and Experimental Lines

Abstract: siagrass genotypes come from diverse origins and are classified as different species. At least five species of Salt tolerant turfgrasses are highly desirable in areas associated zoysiagrass [Zoysia japonica, Z. matrella (L.) Merr., Z. with saline soils and/or saline irrigation waters. To determine the salt tolerance of 29 zoysiagrass (Zoysia spp.) experimental lines and tenuifolia Trin., Z. sinica Hamce, and Z. macrostaycha cultivars, two greenhouse studies were conducted by means of a hy-Franch. & Sav.] and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 11 publications
5
64
1
Order By: Relevance
“…As increasing salinity, K concentration in leachate was increased. This result show the depress effect of high Na levels on K uptake, thereby increasing leaching of K. This is agreement with another study (Qian et al, 2000). Results indicated that the amount of mineral elements including N, K, CA ++ , MG ++ in soil were intensely influenced by zeolite application and increased.…”
Section: Resultssupporting
confidence: 92%
“…As increasing salinity, K concentration in leachate was increased. This result show the depress effect of high Na levels on K uptake, thereby increasing leaching of K. This is agreement with another study (Qian et al, 2000). Results indicated that the amount of mineral elements including N, K, CA ++ , MG ++ in soil were intensely influenced by zeolite application and increased.…”
Section: Resultssupporting
confidence: 92%
“…The increase in biomass refers to high efficient carbon fixation and consequent exchange of growth. We found 50% firing under EC of 2.5 dS m À1 for control while it was as high as 7.5 in transgenic plants, in Zygosiza grass 50% firing was reported under EC of 3.0 dS m À1 (Qian and Engelke 2000). Due to drought and salt stress, the root/shoot ratio significantly increased which is recognized to be a general morphological adaptation to decreased water potentials (Romero- Aranda et al 2002).…”
Section: Discussionmentioning
confidence: 84%
“…(Horst and Beadle 1984), Lolium perenne Wipff 2001), Paspalum vaginatum (Dudeck andPeacock 1985b;Lee et al 2002Lee et al , 2004a, Poa pratensis (Horst and Taylor 1983;Rose-Fricker and Wipff 2001), Stenotaphrum secundatum (Dudeck et al 1993), and Zoysia spp. Qian et al 2000). Such work is important, and needs to be updated at regular intervals, due to the rapid introduction of new cultivars.…”
Section: Turfgrass Salt Tolerance Breedingmentioning
confidence: 99%